Exploring Sexual Obsessions in Obsessive-Compulsive Disorder: Prevalence, Demographic Correlates, and Clinical Implications for Anxiety and Depression - Sharma, Ankuna; Ahmad Lone, Zahoor (Journal of Neonatal Surgery, 2025)
Obsessive-compulsive disorder (OCD) is a severe neuropsychiatric condition that disrupts professional, social, and family lives, often co-occurring with mood disorders like depression. It manifests through obsessions and compulsions, including contamination fears, symmetry, and taboo thoughts. Sexual obsessions cause significant distress, anxiety, shame, and self- disgust, despite sufferers being unlikely to act on them. Aim: This study aimed to explore the demographic and clinical characteristics of OCD patients, with a particular focus on sexual obsessions and their impact on anxiety, depression, and overall functioning. Design: The study employed quantitative, correlational, and descriptive research methods and gathered data using standard psychological instruments. Purposive sampling selected 50 patients, aged 18 to 40, from Ashoka Neuro Psychiatric Hospital & Addiction Centre in Jalandhar (Punjab). Data collection included the Yale-Brown Obsession-Compulsive Disorder Scale (YBOCS) and the Hospital Anxiety and Depression Scale (HADS). Results: Results revealed that sexual obsessions affected 34% of OCD patients, particularly among females, individuals aged 28– 40, married individuals, urban residents, those from joint families, and those with higher education levels. The study also highlighted that OCD patients experience severe symptoms, with 86% reporting severe or intense symptoms and 98% classified as abnormal for anxiety and depression. Cognitive treatment (CT) and exposure and ritual prevention (ERP) therapy were identified as effective interventions for addressing OCD symptoms, including sexual obsessions. Conclusion: The high prevalence of severe OCD symptoms and comorbid anxiety and depression underscores the necessity for early detection and comprehensive treatment. The study emphasises the importance of recognising and addressing sexual obsessions